Anesthesiology or Perioperative Medicine - Rana, Resham Bahadur (Journal of Society of Anesthesiologists of Nepal, 2016)
According to the Department of health services of Nepal, around 100,000 surgical patients received some form of anesthesia for surgical intervention in the year 2014. Around 55,000 were inpatient and 45,000 being outpatient. Many were straight forward, some required optimization prior to anesthesia and surgery. Anesthesiologists are primary physicians who looks patient before, during and after surgeries. Therefore, these specialists have enough knowledge and skills required to be physicians. The article gives a view on development of a specially trained physician, a perioperative physician rather than anesthesiologist and raises a view on transforming the postgraduate degree of anesthesiology from a recognized medical college or university in Nepal to a more appropriate perioperative medicine.